A Double‐Passivation Water‐Based Galvanic Displacement Method for Reproducible Gram‐Scale Production of High‐Performance Platinum‐Alloy Electrocatalysts. Issue 38 (1st July 2019) - Gatalo, Matija; Bele, Marjan; Ruiz‐Zepeda, Francisco; Šest, Ervin; Šala, Martin; Kamšek, Ana Rebeka; Maselj, Nik; Galun, Timotej; Jovanovič, Primož; Hodnik, Nejc; Gaberšček, Miran
Abstract: Preparation of large quantities of high‐performance supported Pt‐alloy electrocatalysts is crucial for the faster development and implementation of low‐temperature proton exchange membrane fuel cells (PEMFCs). One of the prospective nanofabrication synthesis methods is based on the galvanic displacement (GD) reaction. A facile, highly reproducible, gram scale, water‐based double passivation GD method is now presented for the synthesis of carbon‐supported Pt‐M nanoparticles (M=Cu, Ni, Co). It offers great flexibility over the catalyst design, such as the choice of the sacrificial metal (M), variation of the chemical composition of alloy, variation of total metal loading (Pt+M) on carbon support, or even variation of the carbon support itself. The obtained Pt‐alloy catalysts are several times more active compared to a Pt reference and exhibits better stability during accelerated degradation tests performed at 60 °C. Abstract : A double‐passivation galvanic displacement approach for the nanofabrication of supported Pt‐M NPs (M=Cu, Ni, Co) has been developed. The novel method is facile, highly reproducible on a gram scale and is water‐based. The method offers great flexibility for catalyst design, such as the choice of the sacrificial metal (M), variation of the Pt:M chemical composition, and the total metal loading (Pt+M) on a carbon support.